2009
DOI: 10.1159/000222675
|View full text |Cite
|
Sign up to set email alerts
|

Rats Repeatedly Exposed to Toluene Diisocyanate Exhibit Immune Reactivity against Methyl Isocyanate-Protein Conjugates

Abstract: Background: Volatile monoisocyanates are formed through thermal degradation when products containing polyurethane are heated. Repeated exposure to diisocyanates, such as toluene diisocyanate (TDI) are a well-known cause of occupational asthma. However, although monoisocyanates are abundant in occupational settings, there are few data concerning their ability to provoke immune reactions and asthma. We compared immune reactivity and respiratory disease following single or repeated inhalation exposures to the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Isocyanate induces an inflammatory reaction and nonspecific airway hyperresponsiveness, involving type 1 and type 2 immune responses [ 178 ]. It is observed that isocyanate-exposed animals have greater amounts of airway goblet cells, neutrophils, BAL eosinophils, CD4+ T-cells, and ILCs, with a predominant type 2 response [ 179 , 180 ]. Thus, workplace exposure of isocyanate is associated with occupational asthma [ 181 ].…”
Section: Periodontal Response To Orthodontic Force Applicationmentioning
confidence: 99%
“…Isocyanate induces an inflammatory reaction and nonspecific airway hyperresponsiveness, involving type 1 and type 2 immune responses [ 178 ]. It is observed that isocyanate-exposed animals have greater amounts of airway goblet cells, neutrophils, BAL eosinophils, CD4+ T-cells, and ILCs, with a predominant type 2 response [ 179 , 180 ]. Thus, workplace exposure of isocyanate is associated with occupational asthma [ 181 ].…”
Section: Periodontal Response To Orthodontic Force Applicationmentioning
confidence: 99%